Models of care for musculoskeletal health: A cross-sectional qualitative study of Australian stakeholders' perspectives on relevance and standardised evaluation - Briggs, Andrew; Jordan, J.; Speerin, R.; Jennings, M.; Bragge, P.; Chua, Jason; Slater, Helen (2015)
Background: The prevalence and impact of musculoskeletal conditions are predicted to rapidly escalate in the coming decades. Effective strategies are required to minimise 'evidence-practice', 'burden-policy' and 'burden-service' gaps and optimise health system responsiveness for sustainable, best-practice healthcare. One mechanism by which evidence can be translated into practice and policy is through Models of Care (MoCs), which provide a blueprint for health services planning and delivery. While evidence supports the effectiveness of musculoskeletal MoCs for improving health outcomes and system efficiencies, no standardised national approach to evaluation in terms of their 'readiness' for implementation and 'success' after implementation, is yet available. Further, the value assigned to MoCs by end users is uncertain. This qualitative study aimed to explore end users' views on the relevance of musculoskeletal MoCs to their work and value of a standardised evaluation approach. Methods: A cross-sectional qualitative study was undertaken. Subject matter experts (SMEs) with health, policy and administration and consumer backgrounds were drawn from three Australian states. A semi-structured interview schedule was developed and piloted to explore perceptions about musculoskeletal MoCs including: i) aspects important to their work (or life, for consumers) ii) usefulness of standardised evaluation frameworks to judge 'readiness' and 'success' and iii) challenges associated with standardised evaluation. Verbatim transcripts were analysed by two researchers using a grounded theory approach to derive key themes. Results: Twenty-seven SMEs (n = 19; 70.4 % female) including five (18.5 %) consumers participated in the study. MoCs were perceived as critical for influencing and initiating changes to best-practice healthcare planning and delivery and providing practical guidance on how to implement and evaluate services. A 'readiness' evaluation framework assessing whether critical components across the health system had been considered prior to implementation was strongly supported, while 'success' was perceived as an already familiar evaluation concept. Perceived challenges associated with standardised evaluation included identifying, defining and measuring key 'readiness' and 'success' indicators; impacts of systems and context changes; cost; meaningful stakeholder consultation and developing a widely applicable framework. Conclusions: A standardised evaluation framework that includes a strong focus on 'readiness' is important to ensure successful and sustainable implementation of musculoskeletal MoCs.